Preclinical pharmaco-toxicological screening of biomimetic melanin-like nanoparticles as a potential therapeutic strategy for cutaneous melanoma - Marcovici, Iasmina; Chioibas, Raul; Zupko, Istvan; Pinzaru, Iulia; Moaca, Alina; Ledeti, Adriana; Barbu-Tudoran, Lucian; Geamantan, Andreea; Predescu, Iasmina; Dehelean, Cristina Adriana (Frontiers in Pharmacology, 2025)
IntroductionDespite its rarity, cutaneous melanoma (CM) represents the deadliest skin cancer with a high mortality rate, an incidence on the rise, and limited therapeutic options at present. Melanin is a polymeric pigment naturally produced within melanocytes and CM cells that gained a noteworthy attention due to its pharmacological properties, and potential for the design of nanoplatforms with biomedical applications. Up to date, the utilization of melanin-like nanoparticles (MEL-NPs) in cancer treatment has been well-documented, although their efficacy in CM therapy remains scarcely investigated. The current study presents the preclinical evaluation of MEL-NPs as a potential nanomedicine for CM management.MethodsMEL-NPs were produced through the oxidative polymerization of dopamine and characterized via electron microscopy and UV-VIS spectroscopy. The antioxidant activity was determined by using the DPPH method. The cytotoxic, anti-migratory, anti-clonogenic, pro-oxidant and pro-apoptotic properties of MEL-NPs were investigated in vitro by applying the MTT viability test, bright-field and immunofluorescence microscopy, DCFDA/H2DCFDA test, scratch assay, colony formation assay, and RT-qPCR. The irritant and anti-angiogenic effects were assessed in ovo on the vascularized chorioallantoic membrane (CAM).ResultsThe as-made MEL-NPs presented a spherical morphology, an average size of 85.61 nm, a broad UV-VIS absorption spectrum, and a strong antioxidant activity. After a 24 h treatment, MEL-NPs exerted a selective cytotoxicity in SH-4 and B164A5 CM cells compared to HEMa, HaCaT, and JB6 Cl 41-5a healthy skin cells, except for the concentration of 100 µg/mL, at which their viability declined under 70%. Additionally, MEL-NPs accumulated within the intracellular space of CM cells, forming a perinuclear coating, inhibited their motility and clonogenic potential, increased intracellular oxidative stress, targeted the epithelial-to-mesenchymal transition, and induced apoptosis by altering cell morphology, nuclear aspect, F-actin and tubulin distribution, and by modulating the expression of pro- and anti-apoptotic markers. In ovo, MEL-NPs lacked irritant and vascular toxic effects, while exerting an angio-suppressive activity.ConclusionMEL-NPs demonstrated promising anti-melanoma properties, showing a selective cytotoxicity, a strong anti-invasive effect and a pro-apoptotic activity in CM cells, while inhibiting CAM angiogenesis, these novel findings contributing to future research on the potential application of this nanoplatform in CM therapy.